Landscape and Mindscape: A Study of Thinai in the works of two Singaporean Tamil Women Writers ? Kanagalatha and Kamaladevi Aravindan - SANKARAN, CHITRA (2019)
Centering Mobility in Tamil Worlds: Research Agendas for the Twenty-First Century